TELAAH PEMBELAJARAN AL-QUR'AN HADITS MELALUI MEDIA WHATSAPP GRUP DALAM MENGEMBANGKAN KETERAMPILAN MEMBACA AL-QUR’AN PESERTA DIDIK DI MAN 2 MALANG - Aris Ananda; Ika Ratih Sulistiani; Muhammad Fahmi Hidayatullah (VICRATINA, 2021)
MAN 2 Malang is one of the educational institutions that applies distance learning in its implementation due to regulations from the education government in the era of the covid-19 pandemic. This study reviews the study of Al-Qur'an Hadith teachers in developing the ability to read the Qur'an via whatsapp group class 12, as in their learning teachers innovate to maximize their education through skills and methods to students with separate learning conditions in order to run effectively. and efficient, the main questions of this research study are 1) how is the planning, implementation, and evaluation of teachers on the skills of reading the Qur'an of grade 12 students carried out through whatsapp groups, 2) what are the teacher's obstacles and solutions if there are problems or difficulties when learning which was held virtually on 12th grade social media at MAN 2 Malang. To answer the main question, this study uses a qualitative descriptive research approach by composing a theoretical approach study of the sub-sections of the discussion on the results of field research observations. So that the research study can be concluded about the teacher's study in developing the ability to read the Al-Qur'an of students in grade 12 in particular at Madrasah Aliyah Negeri 2 Malang, through planning, implementation, evaluation, and problems and solutions if there are obstacles in the learning process.